1983
DOI: 10.1017/s0022172400063804
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of standard tube and microagglutination techniques for determiningBrucellaantibodies

Abstract: SUMMARYA microagglutination method for determining the agglutinating and 'blocking' antibodies to Brucella abortus is described. A collection of sera from healthy blood donors in two rural areas of New Zealand were tested by the microagglutination methods and the standard methods in tube. The results are compared and show that where discrepancies occur, these are due to the microagglutination methods being more sensitive. It is concluded that these are suitable methods for screening populations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

1984
1984
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 4 publications
(6 reference statements)
1
19
0
Order By: Relevance
“…The SAT and MAT results were comparable with minor differences only and were similar to the findings of Bettelheim, Maskill & Pearce (1983).…”
Section: Discussionsupporting
confidence: 78%
“…The SAT and MAT results were comparable with minor differences only and were similar to the findings of Bettelheim, Maskill & Pearce (1983).…”
Section: Discussionsupporting
confidence: 78%
“…Sensitivity and specificity of MAT with stained antigen have been demonstrated to be comparable or superior to those of the standard tube agglutination test with unstained antigen (Francis and Evans, 1926) in both Francisella (Massey and Mangiafico, 1974;Brown et al, 1980;Sato et al, 1990) and Brucella (Bettelheim et al, 1983;Moyer et al, 1987;Rogers et al, 1989;Sato et al, 1990). We can confirm that MAT compared with the standard tube agglutination 'macrotest' is quicker, easier to perform, more economical (saving sera and antigens) as well as better readable when the sera are haemolytic.…”
Section: Discussionmentioning
confidence: 98%
“…In the present study, the seroprevalence based on ELISA brucellaspecific IgG, IgM and IgA were detected with higher frequency than in SAT or AHGT, most likely due to differences in test sensitivity. For example, Bettelheim and colleagues [37] reported that among 307 healthy blood donors who were negative by SAT, 20 1 % had positive brucella antibodies by AHGT. The sensitivity that of SAT especially in detecting chronic and complicated cases of brucellosis [12,13].…”
Section: Discussionmentioning
confidence: 99%